ENVIRONMENTAL CHEMISTRY OF BERYLLIUM-7 - Kaste J.M.; Norton S.A.; Hess C.T. (My University, 2002)
In addition to the stable isotope 9Be, Be is also formed as two cosmogenic isotopes of interest to earth scientists. Cosmogenic Be is formed primarily in the stratosphere from cosmic-ray spallation of oxygen and nitrogen, but some is produced in the troposphere and in situ on the surface of the earth. Production of cosmogenic Be was hypothesized by Peters (1955). Soon after, naturally occurring 7Be was identified in precipitation by Arnold and Al-Salih (1955) and essentially concurrently and independently by Goel et al. (1956). 10Be (Ti/2= 1.5 x 106yr) was first detected by Arnold (1956) in marine sediment cores. The 10Be / 7Be production ratio is approximately 0.5 (Lai and Peters 1967). After its formation in the atmosphere, cosmogenic Be adsorbs electrostatically to aerosols that may be washed out by precipitation and delivered to ecosystems. The amount of cosmogenic Be that reaches the surface of the earth is a function of production rate (cosmic-ray intensity), stratosphere-troposphere mixing, circulation and advection within the troposphere, and efficiency of removal from the troposphere (wet and dry deposition) (Feely et al. 1989). Since the discovery of cosmic-ray produced Be, numerous researchers have gathered data on its (1) production, (2) fluxes to the oceans and terrestrial ecosystems, (3) distribution and inventory in soils, snow, sediments, and vegetation, and (4) geochemical behavior. In 1955, Peters suggested that the relatively long half-life of 1 Be could make it useful for quantifying Tertiary sedimentation rates and other surficial processes. The focus of this chapter is the short-lived radionuclide 7Be (Tin = 53.12±0.07 days; Jaeger et al. 1996). Due to its short half-life, relative ease of measurement, and well-defined source term, 7Be serves as a useful tool for tracing and quantifying environmental processes on the <1 year timescale (Lai et al. 1958; Young and Silker 1980; Krishnaswami et al. 1980; Russell et al. 1981; Turekian et al. 1983; Dutkiewicz and Husain 1985; Olsen et al. 1985; Wallbrink and Murray 1993; Bonniwell et al. 1999), and has applications in meteorology, soil science, sedimentology, geomorphology, hydrology, geochemistry, and nuclear physics.